2020
DOI: 10.1534/g3.120.401547
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Gliogenesis bylin-32/Atoh1 inCaenorhabditis elegans

Abstract: The regulation of gliogenesis is a fundamental process for nervous system development, as the appropriate glial number and identity is required for a functional nervous system. To investigate the molecular mechanisms involved in gliogenesis, we used C. elegans as a model and identified the function of the proneural gene lin-32/Atoh1 in gliogenesis. We found that lin-32 functions during embryonic development to negatively regulate the number of AMsh glia. The ectopic AMsh cells at least partially arise from cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Furthermore, these glial cells are vital for the proper functioning of the neurons that they ensheath, where they can modulate neural activity through secreted molecules at the receptive endings and control neuron receptive ending shape ( Bacaj et al, 2008 ; Shaham, 2010 ; Singhvi et al, 2016 ). In previous studies we show that the fate determination of C. elegans AMsh glial cells utilizes similar mechanisms as those in mammals ( Zhang et al, 2020a ). AMsh glia are born close to the nose of C. elegans , where their processes anchor to the nose region while the cell bodies migrate toward the nerve ring ( Shaham, 2015 ; Heiman and Shaham, 2009 ), and the position of AMsh glia is important for their function ( Zhang et al, 2020b ).…”
Section: Introductionmentioning
confidence: 73%
“…Furthermore, these glial cells are vital for the proper functioning of the neurons that they ensheath, where they can modulate neural activity through secreted molecules at the receptive endings and control neuron receptive ending shape ( Bacaj et al, 2008 ; Shaham, 2010 ; Singhvi et al, 2016 ). In previous studies we show that the fate determination of C. elegans AMsh glial cells utilizes similar mechanisms as those in mammals ( Zhang et al, 2020a ). AMsh glia are born close to the nose of C. elegans , where their processes anchor to the nose region while the cell bodies migrate toward the nerve ring ( Shaham, 2015 ; Heiman and Shaham, 2009 ), and the position of AMsh glia is important for their function ( Zhang et al, 2020b ).…”
Section: Introductionmentioning
confidence: 73%
“…Four neurons (AWA, AWB, AWC, AFD) form elaborate ciliated endings that are embedded in the wing-shaped portion of the sheath, while the others (ASE, ADF, ASG, ASH, ASI, ASJ, ASK, ADL) terminate in simple cilia that lie in a central lumenal channel [27,30]. Previous genetic screens have identified mutants that affect amphid sheath specification and cell body positioning [31], that disrupt extension of the amphid sheath glial process [9,22], or that lead to enlarged or supernumerary amphid sheath cells [32,33].…”
Section: Resultsmentioning
confidence: 99%
“…NeuroD1 have been shown to regulate neuron-glia fate determination, where they independently promote a neuronal fate while suppressing a glial fate [27][28][29]. Recent studies in C. elegans show that loss of function of the Neurog1 and NeuroD1 orthologs, ngn-1 and cnd-1 respectively, also result in an increase in the number of AMsh glia, which is consistent with a suppression of glial fate [22]. It was also found that LIN-32, an ortholog of the proneural gene Atoh1, functioned similarly.…”
Section: For Example Several Conserved Proneural Transcription Factomentioning
confidence: 97%
“…This article is protected by copyright. All rights reserved glia in lin-32 loss of function mutants came from cells originally fated to become CEPsh glia, suggesting that this proneural transcription factor may also play a role in glial identity specification [22].…”
Section: Accepted Articlementioning
confidence: 99%